Behaviour of different removers on permanent anti-graffiti organic coatings. (March 2016) - Rossi, S.; Fedel, M.; Petrolli, S.; Deflorian, F.
Abstract: Graffiti removal presents high costs in street furniture, transport and architectural facades. Considering painted metallic surfaces, the removal has to be easy and not modify the protective and the aesthetic properties. The study of the interaction between paint and remover and the effects on the anti-graffiti properties is the aim of this paper. Two kinds of polyurethane organic coatings, indicated for metallic substrates, and two different surface finishing were considered. This kind of organic coatings shows a very good corrosion properties connected with the low water uptake together a very interesting aesthetical aspect. The behaviour of methylethylketone, xylene and an aliphatic and aromatic solvent mixture, before and after accelerated weathering, was evaluated. MEK was proven to be particularly aggressive. The wrinkled finishing shows strong criticality. Highlights: The graffiti removal is a current issue. The graffiti removal should not change protection and aesthetic properties. Polyurethane powder coatings could be an efficient permanent anti-graffiti coating. The surface has to maintain the anti-graffiti properties even after weathering.